Ways to Reduce the Negative Effects of the Comparative Resistance of the Soil and the Aggregate Speed of Movement on the Stable Walk of Mounted Plow in Terms of Driving Depth (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article presents the ways to reduce the negative effects of the comparative resistance of the soil and aggregate speed of movement on the stable walk of mounted plow designed for wheel drive tractors in terms of driving depth. According to the results of the conducted theoretical studies, when the vertical distance between the lower suspension points of the suspension device from the base plane of the plow is 0.65 m, the driving depth is reduced by 0.36-1.52 cm with the increase in the specific resistance of the soil and the speed of aggregate movement. When this distance is 0.80 m, it is reduced by 0.12-0.70 cm, that is, the stability of driving depth is improved.